Reinventing identities: the gendered self in discourse - Bucholtz, Mary; Liang, A. C.; Sutton, Laurel A. (Studies in language and gender, 1999)
Talk is crucial to the way our identities are constructed, altered, and defended. Feminist scholars in particular have only begun to investigate how deeply language reflects and shapes who we think we are. This volume of previously unpublished essays, the first in the new series Studies in Language and Gender, advances that effort by bringing together leading feminist scholars in the area of language and gender, including Deborah Tannen, Jennifer Coates, and Marcyliena Morgan, as well as rising younger scholars. Topics explored include African-American drag queens, gender and class on the shopping channel, and talk in the workplace.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; identités LGBTQIA2+; intersectionnalité; lin2685; linguistique; premier cycle; queer; ressource en ligne; sciences humaines; thématiques

Looking queer: body image and identity in lesbian, bisexual, gay, and transgender communities - Atkins, Dawn (Haworth Press, 1998)
Looking Queer: Body Image in Lesbian, Bisexual, Gay, and Transgender Communities contains research, firsthand accounts, poetry, theory, and journalistic essays that address and outline the special needs of sexual minorities when dealing with eating disorders and appearance obsession. Looking Queer will give members of these communities hope, insight, and information into body image issues, helping you to accept and to love your body. In addition, scholars, health care professionals, and body image activists will not only learn about queer experiences and identity and how they affect individuals, but will also understand how some of the issues involved affect society as a whole. Dismantling the myth that body image issues affect only heterosexual women, Looking Queer explores body issues based on gender, race, class, age, and disability. Furthermore, this groundbreaking book attests to the struggles, pain, and triumph of queer people in an open and comprehensive manner. More than 60 contributors provide their knowledge and personal experiences in dealing with body image issues exclusive to the gay and transgender communities, including: exploring and breaking down the categories of gender and sexuality that are found in many body image issues finding ways to heal yourself and your community discovering what it means to “look like a dyke” or to “look gay” fearing fat as a sign of femininity determining what race has to do with the gay ideal discussing the stereotyped ”double negative”--being a fat lesbian learning strategies of resistance to societal ideals critiquing ”the culture of desire” within gay men’s communities that emphasizes looks above everything else Revealing new and complex dimensions to body image issues, Looking Queer not only discusses the struggles and hardships of gay, lesbian, bisexual, and transgendered persons, but looks at the processes that can lead to acceptance of oneself. Written by both men and women, the topics and research in Looking Queer offer insight into the lives of people you can relate to, enabling you to learn from their experiences so you, too, can find joy and happiness in accepting your body.
Keywords: LGBTQIA2+; amériques; anthropologie; approches et analyses; cours; discipline; image corporelle; intersectionnalité; premier cycle; queer; régions géographiques; sciences humaines; soc2014; thématiques; troubles alimentaires; états-unis

Inside the academy and out: lesbian/gay/queer studies and social action - Ristock, Janice L.; Taylor, Catherine G. (University of Toronto Press, 1998)
Inside the Academy and Out demonstrates that the pedagogical and theoretical insights offered by lesbian/gay/queer studies can have relevance to a broader social sphere. The essayists represented here come from a wide range of disciplines, including English, education, philosophy, sociology, and women's studies. Their essays are divided into two broad areas: 'Pedagogy and Research' and 'Spheres of Action.' Taken together, they explore teaching and research theory, examining their implications in areas such as AIDS education, social services, law reform, and popular culture.
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; approches et analyses; cours; discipline; droit; ethnographie; intersectionnalité; justice sociale; militance; premier cycle; pédagogie; périodes historiques; queer; santé; science politique et droit; sciences de l'éducation; sciences humaines; sexologie; soc2014; thématiques; violences

Re-orienting western feminisms: Women's diversity in a postcolonial world - Bulbeck, Chilla (Cambridge University Press, 1997)
The agenda of contemporary western feminism focuses on equal participation in work and education, reproductive rights, and sexual freedom. But what does feminism mean to the women of rural India who work someone else's fields, young Thai girls in the sex industry in Bangkok, or Filipino maids working for wealthy women in Hong Kong? In this 1998 book, Chilla Bulbeck presents a bold challenge to the hegemony of white, western feminism in this incisive and wide-ranging exploration of the lived experiences of 'women of colour'. She examines debates on human rights, family relationships, sexuality, and notions of the individual and community to show how their meanings and significance in different parts of the world contest the issues which preoccupy contemporary Anglophone feminists. She then turns the focus back on Anglo culture to illustrate how the theories and politics of western feminism are viewed by non-western women.
Keywords: approches et analyses; asie; cours; discipline; fem1000; féminisme postcolonial; inde; intersectionnalité; militance; premier cycle; ressource en ligne; régions géographiques; sciences humaines; sociologie; thématiques

La collaboration à travers les différences : quelques réflexions sur les émotions et la pratique politique - Narayan, Uma (Canadian Journal of Women and the Law, 1993)
Uma Narayan tente de clarifier le contenu de la notion féministe de "privilège épistemique des opprimé-es". Elle soutient que le privilege épistémique des "initié-es" opprimé-es concernant leur oppression suscite des problèmes de dialogue et de politique de coalition avec les "non-initié-es" qui eux, ne subissant pas cette oppression, n'arrivent pas à se réconcilier au privilege épistémique des initié-es. Elle analyse concrètement comment les non-initié-es peuvent par inadvertance blesser les initié-es, et elle propose des moyens permettant de minimiser ces problèmes.
Keywords: approches et analyses; discipline; injustices épistémiques; intersectionnalité; inégalités; militance; privilèges; ressource en ligne; science politique; science politique et droit; sciences humaines; systèmes d'oppressions; thématiques; émotions; épistémologie

Unruly women: The politics of social and sexual control in the old South - Bynum, Victoria E. (Gender & American culture, 1992)
In this richly detailed and imaginatively researched study, Victoria Bynum investigates "unruly" women in central North Carolina before and during the Civil War. Analyzing the complex and interrelated impact of gender, race, class, and region on the lives of black and white women, she shows how their diverse experiences and behavior reflected and influenced the changing social order and political economy of the state and region. Her work expands our knowledge of black and white women by studying them outside the plantation setting.Bynum searched local and state court records, public documents, and manuscript collections to locate and document the lives of these otherwise ordinary, obscure women. Some appeared in court as abused, sometimes abusive, wives, as victims and sometimes perpetrators of violent assaults, or as participants in illicit, interracial relationships. During the Civil War, women frequently were cited for theft, trespassing, or rioting, usually in an effort to gain goods made scarce by war. Some women were charged with harboring evaders or deserters of the Confederacy, an act that reflected their conviction that the Confederacy was destroying them.These politically powerless unruly women threatened to disrupt the underlying social structure of the Old South, which depended upon the services and cooperation of all women. Bynum examines the effects of women's social and sexual behavior on the dominant society and shows the ways in which power flowed between the private and public spheres. Whether wives or unmarried, enslaved or free, women were active agents of the society's ordering and dissolution.
Keywords: 1800-1899; amériques; approches et analyses; civil war; cours; discipline; féminisme matérialiste; his4443; histoire; histoire des femmes*; histoire et politique; intersectionnalité; premier cycle; périodes historiques; racisme; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sexualité; systèmes d'oppressions; thématiques; violences; états-unis

Les femmes autochtones et la justice pénale - Jaccoud, Mylène (Criminologie, 1992)
The interest in understanding and analyzing the situation of native women within the penal process is recent and seems to be limited by the inordinate attention paid by researchers to the overrepresentation of native women. This article is an account of the findings and analyses made to date in this recent sector of research. It presents an inventory of the principal data concerning the confrontation of native women with the penal process. It proposes a synthesis of the principal analyses of the problems of native women with the system of justice by presenting a critical analysis of the socio-structural model of LaPrairie.
Keywords: amériques; approches et analyses; canada; cours; criminologie; discipline; droit; droits des femmes*; droits des femmes* autochtones; histoire et politique; intersectionnalité; justice sociale; pol4105; premier cycle; racisme; régions géographiques; science politique et droit; sciences humaines; sexisme; système colonial; systèmes d'oppressions; thématiques; violences